Changing climate and the altitudinal range of avian malaria in the Hawaiian Islands – an ongoing conservation crisis on the island of Kaua'i. (27th February 2014) - Atkinson, Carter T.; Utzurrum, Ruth B.; Lapointe, Dennis A.; Camp, Richard J.; Crampton, Lisa H.; Foster, Jeffrey T.; Giambelluca, Thomas W.
Abstract Transmission of avian malaria in the Hawaiian Islands varies across altitudinal gradients and is greatest at elevations below 1500 m where both temperature and moisture are favorable for the sole mosquito vector, Culex quinquefasciatus, and extrinsic sporogonic development of the parasite, Plasmodium relictum. Potential consequences of global warming on this system have been recognized for over a decade with concerns that increases in mean temperatures could lead to expansion of malaria into habitats where cool temperatures currently limit transmission to highly susceptible endemic forest birds. Recent declines in two endangered species on the island of Kaua'i, the 'Akikiki (Oreomystis bairdi) and 'Akeke'e (Loxops caeruleirostris), and retreat of more common native honeycreepers to the last remaining high elevation habitat on the Alaka'i Plateau suggest that predicted changes in disease transmission may be occurring. We compared prevalence of malarial infections in forest birds that were sampled at three locations on the Plateau during 1994–1997 and again during 2007–2013, and also evaluated changes in the occurrence of mosquito larvae in available aquatic habitats during the same time periods. Prevalence of infection increased significantly at the lower (1100 m, 10.3% to 28.2%), middle (1250 m, 8.4% to 12.2%), and upper ends of the Plateau (1350 m, 2.0% to 19.3%). A concurrent increase in detections of Culex larvae in aquatic habitats associated with stream margins indicates that populations of the vector are also increasing. These increases are at least in part due to local transmission because overall prevalence in Kaua'i 'Elepaio (Chasiempis sclateri), a sedentary native species, has increased from 17.2% to 27.0%. Increasing mean air temperatures, declining precipitation, and changes in streamflow that have taken place over the past 20 years are creating environmental conditions throughout major portions of the Alaka'i Plateau that support increased transmission of avian malaria.